Trade invoicing in the accession countries: Are they suited to the euro? - Linda S. Goldberg (Federal Reserve Bank of New York, 2005)
Countries aspiring to join the euro area—the so-called accession countries—are increasingly binding their economic activity, external and internal, to the euro-area countries. This phenomenon is observed in the currency invoicing of international trade transactions, where accession countries have reduced their use of the U.S. dollar in invoicing such transactions. According to theory, the optimal invoicing choice for an accession country depends on its composition of exports and imports and on the macroeconomic fluctuations faced by its trade partners, with both factors bearing out the role of herding and hedging considerations within exporter profitability. These considerations yield country-specific estimates of the optimal degree of euro-denominated invoicing of exports. I find that the exporters in some accession countries might be pricing too much of their trade in euros rather than in U.S. dollars, even in their trade transactions with the euro-area and other European Union countries, and thus may be taking on excessive risk in international markets.
Keywords: F3; F4; 330; exchange rate pass-through; invoicing; trade; vehicle currency; accession country; euro area; Währungswettbewerb; Euro; Exchange Rate Pass-Through; Export; EU-Erweiterung; EU-Staaten